Polidocanol versus hypertonic glucose for sclerotherapy treatment of reticular veins of the lower limbs: study protocol for a randomized controlled trial - Bertanha, Matheus; Sobreira, Marcone Lima; Pinheiro Lúcio Filho, Carlos Eduardo; de Oliveira Mariúba, Jamil Victor; Farres Pimenta, Rafael Elias; Jaldin, Rodrigo Gibin; Moroz, Andrei; Moura, Regina; Rollo, Hamilton Almeida; Yoshida, Winston Bonetti (Trials, 2014)
The prevalence of chronic venous disease is high and occurs more frequently in females. According to the clinical, etiological, anatomical, and pathological classification (CEAP) definition, the reticular veins are included in the C1 class and are mainly associated with aesthetic complaints. Several invasive techniques are used for treatment, including mini phlebectomy, laser ablation, and radiofrequency ablation. However, a wide range of sclerosing agents may serve as minimally invasive alternatives, promoting chemical sclerosis of the vein wall. Although this technique is routinely performed around the world, there is no consensus on the most efficacious and safe chemical agent to be used. Inclusion criteria are women between 18 and 69 years old with at least 10 cm long reticular veins in the lower limbs, on the outer side of the leg/thigh. Patients with CEAP 2 to 6, or with allergies, pregnancy, performing breastfeeding, or with any dermatologic or clinical problems will be excluded. Patients with venous ultrasound mapping showing involvement of saphenous trunks and/or a deep venous system will also be excluded. Patients will be randomized into two groups, one receiving 75% pure glucose and the other group receiving 0.2% polidocanol diluted in 70% glucose. Just one limb and one session per patient will be performed. The sclerosing agent volume will not exceed 5 mL. Clinical follow-up will include visits on days 7 and 60, always with photographic documentation. This project aims to enroll 96 patients and subject them to a double-blind treatment after the randomization process. The design is intended to evaluate efficacy through a primary end point and safety through a secondary end point. Forty-eight patients have currently been enrolled. Preliminary results for these patients showed that 25 received treatment, 2 were excluded, and 22 returned after 7 days and showed no greater adverse events. To date, establishing efficacy criteria has not been possible, and no patients have reached the 60-day return point. These data may help doctors choose the best chemical agent for the treatment of reticular veins. ClinicalTrials.gov Identifier: NCT02054325, 3/02/2014.